Developing and Testing HOTS-Based Evaluation Packages for Metabolism with Science Literacy Skills Aspects - Sepe, Caecelia Pascella Avianty; Aquan, Hendra Michael (IJECA (International Journal of Education and Curriculum Application), 2023)
The purpose of learning evaluation is to measure students' higher-order thinking skills (HOTS) and science literacy skills. However, many challenges hinder this process, such as low-level questions, lack of question variety, student dishonesty, and poor reading comprehension and understanding of questions. These factors reduce students' reasoning abilities and learning outcomes. Therefore, this study aims to develop and test the feasibility of an evaluation package that emphasizes HOTS and science literacy skills in the topic of metabolism. Metabolism is a difficult topic for students because it covers a wide range of complex and abstract concepts. This study used the Research and Development (R&D) method with the ADDIE model, which was limited to the Development stage. The research stages consisted of needs analysis, design and development, as well as product validation and revision. Data collection was done through interviews and validation questionnaires and analyzed using quantitative and qualitative data. The results of this study were two packages of HOTS questions (A and B) with aspects of science literacy skills, each containing 20 questions with 100% HOTS proportion and five different question formats. The questions were printed on A4 paper and intended to be used as daily test assessments. The results of the validation showed that both packages were "very feasible" with a percentage of 91.6% (Package A) and 92% (Package B). Therefore, the evaluation package developed was suitable for limited testing after revision.